If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -9 = 6y + 116 Reorder the terms: -9 + y = 6y + 116 Reorder the terms: -9 + y = 116 + 6y Solving -9 + y = 116 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -9 + y + -6y = 116 + 6y + -6y Combine like terms: y + -6y = -5y -9 + -5y = 116 + 6y + -6y Combine like terms: 6y + -6y = 0 -9 + -5y = 116 + 0 -9 + -5y = 116 Add '9' to each side of the equation. -9 + 9 + -5y = 116 + 9 Combine like terms: -9 + 9 = 0 0 + -5y = 116 + 9 -5y = 116 + 9 Combine like terms: 116 + 9 = 125 -5y = 125 Divide each side by '-5'. y = -25 Simplifying y = -25
| 6q=9q-7 | | 0.7X-16=1.3x-19 | | 2a+13-8=14 | | -5(4y-7)-y=-4(y-5) | | 3(x^2-2x-2)=0 | | -5(4y-7)=-4(y-5) | | x^3+8x^2+32X=0 | | (5x-2)+(2x-1)-(3x+4)= | | (19b-2)-6(3b+1)=-4 | | 17x+1=4(4x+8) | | -3(5p+3)-2(4-11p)=3(6+2p) | | 3x-6-5=-7 | | 32z+9+12=10 | | 24+9y=-3y | | (9k-6)(7k-3)= | | (2x^3-6x^2+5)-(-6x^3+7x-5)= | | -3(4s-3)-9=-3(6s+2)-3 | | (2x^3-3x^2+2)-(-7x^3-2x-3)= | | 2x+5(x-7)=8x+9 | | -4.9t^2+30t+16=0 | | 303=8.5x | | 108=10x | | 8x^5(9x^7)= | | 3ln(x-2)=ln(x+1) | | (11b-8)-5(2b+1)=-6 | | 2(x+6)=9x-12 | | 12x+34x+14=0 | | 100-20t=-40 | | 100-20t=40 | | x+2x+(5x+1)=33 | | 13+16q= | | 4x-48=8(x-7) |